2017
DOI: 10.1371/journal.pone.0181550
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pre-surgical administration of prostaglandin analogs on the outcome of trabeculectomy

Abstract: For primary open angle glaucoma (POAG), laser treatment or surgery is used when the target intraocular pressure (IOP) cannot be achieved by pharmacological agents, such as prostaglandin (PG) analogs; these drugs also have varied effects. We retrospectively reviewed the medical records of 74 POAG patients (74 eyes) whose IOP was inadequately controlled by PG analogs (bimatoprost [13 eyes], latanoprost [34 eyes], tafluprost [11 eyes], and travoprost [16 eyes]) and underwent primary trabeculectomy. The proportion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 35 publications
0
23
0
5
Order By: Relevance
“…A recent Japanese study found better IOP control post-trabeculectomy in those patients who did not exhibit signs of orbitopathy due to preoperative prostaglandin analogues. 58 …”
Section: Introductionmentioning
confidence: 99%
“…A recent Japanese study found better IOP control post-trabeculectomy in those patients who did not exhibit signs of orbitopathy due to preoperative prostaglandin analogues. 58 …”
Section: Introductionmentioning
confidence: 99%
“…The presence of DUES makes it difficult to measure IOP by Goldmann applanation tonometry, and Miki et al reported that preoperative use of bimatoprost might be related to recurrent IOP elevation after trabeculectomy. 42 To the best of our knowledge, ripasudil-associated DUES has not been reported. However, blepharitis and conjunctivitis sometimes occur during ripasudil treatment and are among the major reasons for treatment discontinuation.…”
Section: Patient Selectionmentioning
confidence: 87%
“…Простагландины ингибируют адипогенез и уменьшают объем орбитальной клетчатки, что в среднем у 24 % больных ведет к орбитопатии и углублению борозды верхнего века в 50 % при использовании биматопроста, в 28 % -травопроста, в 17 % -латанопроста и лишь в 6 % -тафлупроста [37,38]. Подобные изменения на фоне применения тафлупроста без консервантов, как и бримонидина, не развиваются [39,40].…”
Section: переносимость антиглаукомной терапии и побочные эффекты актиunclassified
“…Кроме того, аналоги простогландинов и β-адреноблокаторы нарушают стабильность слезной пленки и снижают слезопродукцию. Травопрост влияет на эти параметры в меньшей степени, чем биматопрост [45], а терапия тафлупростом, напротив, через три месяца приводит к увеличению времени разрыва слезной пленки [36][37][38][46][47][48]. Минимальное действие на стабильность слезы и слезопродукцию оказывает латанопрост -время разрыва слезной пленки сохраняется у всех пациентов на уровне 10 с и более, а высота слезного мениска остается неизменной в течение года [29,49].…”
Section: переносимость антиглаукомной терапии и побочные эффекты актиunclassified
See 1 more Smart Citation